Modes of delivery in preventive intervention studies: a rapid review. (July 2014) - Beall, Reed F.; Baskerville, Neill; Golfam, Mohammad; Saeed, Sara; Little, Julian
Abstract Background This review was commissioned to generate broad discussion about how to select intervention delivery modes when designing a complex, preventive intervention aimed at chronic disease through the promotion of physical activity, healthy diet and/or medication adherence. In this context, we asked, what are the delivery modes? What are the important design considerations? And how do these compare (e.g. strengths, limitations)? Materials and methods This review utilized the methods of rapid review, an emerging methodology arising from health technology assessment. The search strategy was applied in Embase and MEDLINE. A qualitative, narrative synthesis was performed on included articles. Results After screening, 21 articles remained for synthesis (10 systematic reviews, including 1 review of reviews; four trials or studies; three commentaries or conference proceedings; and 2 were scoping projects). Our synthesis determined that major categories of design considerations when selecting intervention delivery modes include attention to the (i) candidate mode types, (ii) settings and social environment, (iii) intensity and timing, (iv) provider, (v) study population and participants, (vi) cost, (vii) behaviour change technique and (viii) theoretical basis. Conclusion An array of modes of delivery is available for each of the intervention strategies under consideration (i.e. physical activity, dietary change and medication adherence). No single delivery mode was clearly more appropriate or more effective than another, each having unique strengths and limitations. Delivery mode decisions that take the above‐mentioned factors (i–viii) into account will be more fit‐for‐purpose than those that do not.